Peer Review - A Comprehensive Study on the Influence of Strength and Stiffness eccentricities to the On-plan Rotation of Asymmetric Structure - Ade Faisal (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
All buildings are subjected to some degree of torsion which in turn changes the member torsional demands from that of translation only. Torsional effects on buildings subjected to earthquakes are not found directly in structural analysis unless full three-dimensional inelastic dynamic time history analysis is conducted. Since design is often conducted using two-dimensional analysis, these effects are not directly considered. There is currently an understanding on how different factors may influence torsion, however, the degree to which these factors influence torsion is relatively unknown. Slab rotation effect is considered a major response parameter to represent the severity of the torsional response of eccentric systems; hence, it is considered in this study. The centre of strength (CR) and centre of stiffness (CS) are the two main factors under considerations. A comprehensive analysis on eighty different CR and CS conditions are applied to a three-dimensional, asymmetric building and their influences to slab rotation are observed. The CR/CS conditions are applied by varying strength eccentricities (er) and stiffness eccentricities (es) using two condition models. Then, earthquake ground motions are applied in z-direction under elastic and inelastic conditions. The results interpreted using a simple approach shows important slab rotation behaviour that forms interesting findings from this study. The slab rotation demand is found to reduce as strength eccentricity moves away from the Centre of Mass (CoM) but is independent of the stiffness eccentricity. The study also confirms finding of previous works which states that stiffness eccentricity plays a minor role when assessing the torsional behaviour of a ductile systems. Results from inelastic analysis shows slab rotation demand increases as strength eccentricity is closer to the CoM but it remains constant for elastic analysis.